ANALISIS KEMAMPUAN KEMAMPUAN PENALARAN DAN SELF CONFIDENCE SISWA SMA DALAM MATERI PELUANG - Anisa Nur Diniyah; Gaza Ahmad Malik Akbar; Padillah Akbar; Adi Nurjaman; Martin Bernard (Journal on Education, 2018)
This research is based on the level of mathematical reasoning ability and Self confidence which is owned by Students who are still relatively low. then the purpose of this study are: 1) to know the level of students' reasoning ability seen from the achievement of minimum mastery criteria (KKM); 2) to know the students' perceptions of each indicator of mathematical reasoning ability; 3) to know the level of Self confidence categories of students on each item statement. This research uses qualitative approach with explorative descriptive method. Subjects in this study were students of class XI IPS1 which amounted to 20 students in SMA Putra Juang academic year 2017/2018. The research instrument consisted of test question instrument, non test instrument in the form of questionnaire, and interview guide. From the research, it is found that the reasoning ability and self confidence of XI IPS1 SMA Putra Juang class students on the opportunity material are included in low category. This can be seen from the test results where the value of Students 75% below KKM and only 25% above KKM.Serta from the questionnaire that shows the ability of self-confidence mathematics owned 50% low students, 25% Medium, 20% High, and 5 % very high. whereas students 'misconception in reasoning ability occurs in many indicators of students' ability to construct and test a conjecture in mathematics lessons, where only 5 students reach this indicator of ability.